Piúma (ES)-"Cidade das conchas" : uma análise do artesanato como ícone de patrimônio local - Lopes, Adriana Tiago (2016)
This research aims to understand the relationship between craft, the intangible cultural heritage, collective memory and identity, analyzing the influence of one over the other. Therefore, we conducted a field study among the artisans and residents of Piu